THE RELATIONSHIP OF WORK DISCIPLINE, WORK MOTIVATION, JOB SATISFACTION, AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE MEDICAL RECORDS IN ISLAMIC HOSPITALS JAKARTA CEMPAKA PUTIH - Abul A'la Al Maududi; Shafa Kemala Fitri (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Employee performance is quite important for the success of an organization in a highly competitive world of work, as for factors that influence performance, namely discipline, motivation, satisfaction, and environment. This study's goal was to ascertain how RSIJ Cempaka Putih Medical Records personnel's performance was impacted by their work environment, motivation, discipline, and job satisfaction. Methods: This kind of research is quantitative and uses a cross-sectional methodology. 48 employees of RSIJ Cempaka Putih who worked in medical records made up the study's population and were used as respondents (total sampling). The chi-square correlation test indicates a p = 0.007 (p < 0.05) association between work discipline and employee performance. employee performance and job motivation, with p = 0.000 (p < 0.05). employee performance and job satisfaction, with p = 0.001 (p < 0.05). impact of the workplace on worker performance, with p = 0.013 (p < 0.05). In conclusion, employee performance is influenced by work environment, job happiness, work motivation, and work discipline. To enhance employee performance in the future, it is anticipated that workers will focus on elements that can enhance their performance rather than just the variables in this study. Additionally, RSIJ Cempaka Putih should provide greater attention and oversight to its staff members, both in terms of work motivation and work discipline.